2013
DOI: 10.12968/bjcn.2013.18.5.234
|View full text |Cite
|
Sign up to set email alerts
|

The expansion of nurse prescribing in Scotland: an evaluation

Abstract: Medicine prescribing by community nurses commenced in the UK in 1996. By 2001, nurse prescribing was extended to include more nurses and to cover a wider formulary. This research project provides an evaluation of the extension of prescribing powers to nurses in Scotland, following the introduction of legislation in 2001. It aimed to evaluate the impact of nurse prescribing powers on patients, nurses, prescribers, and other stakeholders. A range of methods were used, including two public surveys, stakeholder in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…The comments from line managers concur with findings from other studies which have identified the learning in practice experience as being crucial to support the development of specialist prescribing practice within a generic programme (Coull et al 2013;Bissell, et al, 2008;George, et al, 2007). Line managers saw practice learning time as being one of the most beneficial parts of the programme.…”
Section: Discussionsupporting
confidence: 76%
“…The comments from line managers concur with findings from other studies which have identified the learning in practice experience as being crucial to support the development of specialist prescribing practice within a generic programme (Coull et al 2013;Bissell, et al, 2008;George, et al, 2007). Line managers saw practice learning time as being one of the most beneficial parts of the programme.…”
Section: Discussionsupporting
confidence: 76%
“…A mixed methods study reported that the benefits of nurse prescribing included a positive impact on patient care and team working, as well as higher patient satisfaction in relation to receiving medicine related information (Jones, Edwards, & While, 2011). An evaluation of nurse prescribing in Scotland revealed similar benefits, including improved patient access to treatment, enhanced professional satisfaction and inter-professional working (Coull, Murray, Turner-Halliday, & Watterson, 2013). Drennan et al (2011) surveyed 140 patients and parents of paediatric patients and found that both patients and parents were highly satisfied with the care received from nurse and midwife prescribers and highlighted the comprehensive education and advice on medications they received.…”
Section: Introductionmentioning
confidence: 98%
“…[13] Jones in 2011, described the roles of prescribers and their effects on patient satisfaction in acute settings in England. [14]…”
Section: Introductionmentioning
confidence: 99%